Temporomandibular disorder severity and its association with psychosocial and sociodemographic factors in Turkish adults - Mehmet Melih Omezli; Damla Torul; Ceren Varer Akpinar (BMC Oral Health, 2023)
Abstract Background There is a lack of awareness regarding temporomandibular disorder (TMD) and its association with psychological and sociodemographic factors in the Turkish population. This study aimed to evaluate the relationship between signs/symptoms of anxiety-depression, sociodemographic factors, parafunctional habits, bruxism, and the presence and severity of the symptoms of TMD in Turkish adults. Methods The participants completed an online questionnaire consisting of sociodemographic questions, the Fonseca Anamnestic Index, and the Patient Health Questionnaire-4. Results The mean age of the 2580 participants was 35.29 ± 12.70 years, and 63.3% were women. The frequency of the participants who showed symptoms of TMD was 69.8%. The severity of TMD symptoms was significantly greater in participants who had signs/symptoms of anxiety and depression (p < 0.05). Sociodemographic and psychological data showed an association between the presence and severity of the symptoms of TMD and sex (OR 1.52, 95% confidence interval (CI) 1.26–1.85), parafunctional habits (OR 2.64, 95% CI 2.36–2.99), bruxism (OR 3.14, 95% CI 1.78–4.90), signs/symptoms of anxiety (OR 2.30, 95% CI 1.76–3.00), and signs/symptoms of depression (OR 1.90, 95% CI 1.48–2.42). Conclusions The results of the present study suggest that females and those who report bruxism, parafunctional habits, and signs/symptoms of anxiety-depression are more likely to show symptoms of TMD with different severity.